Implementation of the Family Support Group on the Recovery of Drug Abuse Victims in the Rehabilitation Institutions for the Management and Abuse of Drugs (LRPPN) Medan - Febriantika Febriantika; Muhammad Badiran; Ayi Darmana (Newinera Publisher, 2020)
This study aims to determine the successful implementation of the Family Support Group (FSG) in the recovery process of victims of drug abuse who participate in the rehabilitation program at the LRPPN BI Institute in Medan. The subjects in this study were counselees (residents), while the key informants in this study included counselors, families and victims of drug abuse. This research is a descriptive qualitative approach. The method of collecting data through the method of observation, interviews and documentation. The results of this study indicate that the implementation of the Family Support Group (FSG) in the recovery process of victims of drug abuse can improve self-concept, reduce anxiety, develop responsibility and be aware of their abilities, both within the family and in the community. The family plays an important role in the recovery process of the counselee (resident) to return to live a healthy life without using drugs, the family can keep the child from relapse (relapse) consume drugs. As for the obstacles in the implementation of the Family Support Group (FSG) such as divorced and remarried parents, busyness of the family due to work and the geographical location of the counselee's family (resident) with the location of the BI LRPPN Medan which is quite far away.